2016
DOI: 10.1002/da.22473
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Depressed Patients Respond Less Well to Antidepressants in the Short Term

Abstract: Antidepressant treatment seems to be less effective among those patients that need it most. Clinical trials including suicidal patients are needed to investigate specific treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 66 publications
(75 reference statements)
3
27
0
Order By: Relevance
“…Our findings suggest a vicious circle in which more vulnerable patients (those more severely depressed, having more suicidal thoughts and pain) are less adherent to medication, which could worsen the clinical picture maintaining, in turn, low adherence. In this sense, it has been reported that antidepressant treatment seems to be less effective among depressed patients presenting suicidal ideation (i.e., thus more severely ill), compared to those depressed without suicidal thoughts (Lopez‐Castroman, Jaussent, Gorwood, & Courtet, ). Probably adherence to treatment, which was not explored in this study, could help to understand these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest a vicious circle in which more vulnerable patients (those more severely depressed, having more suicidal thoughts and pain) are less adherent to medication, which could worsen the clinical picture maintaining, in turn, low adherence. In this sense, it has been reported that antidepressant treatment seems to be less effective among depressed patients presenting suicidal ideation (i.e., thus more severely ill), compared to those depressed without suicidal thoughts (Lopez‐Castroman, Jaussent, Gorwood, & Courtet, ). Probably adherence to treatment, which was not explored in this study, could help to understand these findings.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all anxiety scales were associated with suicidal ideation. Suicidality itself has been noted in some studies as a predictor of poor short-term treatment response (Lopez-Castroman, Jaussent, Gorwood, & Courtet, 2016;Szanto, Mulsant, Houck, Dew, & Reynolds, 2003). For instance, Szanto et al (2003) showed that older depressed patients with high levels of suicidality both had a long time to respond and were less likely to fully respond to treatment.…”
mentioning
confidence: 99%
“…Third, one cannot exclude that ACT improved the severity of suicidal ideation through improvements in depression. Should that be the case, it might still represent a worthwhile path to reducing suicidal ideation, given that antidepressants have been shown to be less effective in suicidal patients [57]. Fourth, given the number of comparisons being performed on secondary outcomes, the risk of chance findings may be increased.…”
Section: Discussionmentioning
confidence: 99%